Teaching botany through making soaps of medicinal plants - Alcilene Bezerra; Dryelle Vieira Rodrigues; Felipe Sant' Anna Cavalcante; Patrícia Guedes Nogueira; Renato Abreu Lima (Universidade Federal de Rondônia, 2018)
Medicinal plants have been used since the dawn of mankind. Vegetable soaps have a greater benefit to human health and the environment, since the chemical composition of the soaps is relatively smaller when compared to commercial soap. In this sense, this work had the objective of making soaps using essences of medicinal plants of the Amazon Region associating with the knowledge in Botany. The work was developed in a full-time school in the municipality of Porto Velho-RO with 120 high school students. The essences of banana, açaí, cupuaçu and buritiwere obtained from free trade shows in Porto Velho-RO. At the school, a pre and a questionnaire was applied in order to get information about the botany in daily life. Then, an oral presentation was made using multimedia resources to perform the work and later, a practical classroom lesson using materials such as: glycerin, essences, natural dye, oven and silicone forms. It was verified that the students understood in a contextualized way the importance of the medicinal plants and their relation with the teaching of Botany, starting to identify that the plants are part of the daily life, thus presenting importance in the area of scientific research